1998
DOI: 10.1017/s0963548398003526
|View full text |Cite
|
Sign up to set email alerts
|

The Size of the Giant Component of a Random Graph with a Given Degree Sequence

Abstract: Given a sequence of non-negative r e a l n umbers 0 1 : : :which s u m t o 1 , w e consider a random graph having approximately i n vertices of degree i. In 12] the authors essentially show that if P i(i ; 2) i > 0 then the graph a.s. has a giant component, while if P i(i ; 2) i < 0 then a.s. all components in the graph are small. In this paper we analyze the size of the giant component in the former case, and the structure of the graph formed by deleting that component. We determine 0 0 0 1 : : : such that a.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
705
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 720 publications
(728 citation statements)
references
References 11 publications
18
705
0
5
Order By: Relevance
“…We assume that all N i nodes in network i are randomly assigned a degree k from a probability distribution P i (k), and are randomly connected with the only constraint that the node with degree k has exactly k links 91 . We define the generating function of the degree distribution…”
Section: Generating Functions For a Single Networkmentioning
confidence: 99%
“…We assume that all N i nodes in network i are randomly assigned a degree k from a probability distribution P i (k), and are randomly connected with the only constraint that the node with degree k has exactly k links 91 . We define the generating function of the degree distribution…”
Section: Generating Functions For a Single Networkmentioning
confidence: 99%
“…However, by using techniques in Lemma 1 of [15], it can be shown that if a random graph with a given degree sequence a. s. has property P under one of these two models, then it a. s. has property P under the other model, provided some general conditions are satisfied.…”
Section: I{vldeg(v) = X} I= Y = ~-Z"mentioning
confidence: 99%
“…. , n), the configuration model produces a random graph with specified degrees [32,36,37]: initially, each vertex i is assigned d i "stubs" or "half edges." Then, the edge set is constructed as a uniformly random matching on the stubs, i.e., each matching is selected with equal probability.…”
Section: K-nearest Neighbor Random Graphsmentioning
confidence: 99%